Assessment of loading history of compartments in the knee using bone SPECT/CT: A study combining alignment and 99mTc‐HDP tracer uptake/distribution patterns. Issue 2 (8th August 2012) - Hirschmann, Michael T.; Schön, Stephan; Afifi, Faik K.; Amsler, Felix; Rasch, Helmut; Friederich, Niklaus F.; Arnold, Markus P.
Abstract This study investigates if the mechanical/anatomical alignment influences the intensity values as well as the distribution pattern of SPECT/CT tracer uptake. Eighty‐five knees (mean age 48 ± 16) undergoing 99mTc‐HDP‐SPECT/CT due to pain were prospectively included. SPECT/CTs were analyzed using a previously validated localization method. The maximum intensities in each femoral, tibial, and patellar joint compartment (medial, lateral, central, superior, and inferior) were noted using a color‐coded grading scale (0–10). The Kellgren–Lawrence osteoarthritis score (KL) was assessed on standardized radiographs. Long leg radiographs were used to assess the mechanical/anatomical leg alignment, which was classified as varus, valgus, or neutral. The alignment and KL was correlated with the intensity of tracer uptake in each area of interest (p < 0.05). The intensity of SPECT/CT tracer uptake in the medial and lateral knee compartment significantly correlated with varus or valgus alignment of the knee. A higher degree of osteoarthritis was significantly related to higher tracer uptake in the corresponding joint compartments. SPECT/CT reflects the specific loading pattern of the knee with regard to its alignment. It is also related to the degree of osteoarthritis. Hence, SPECT/CT should be considered for follow‐up of patients after realignment treatments, osteotomies, deloader devices, or insoles. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 268–274, 2013